Belief, Superstition, and Popular Customs in Medieval Galicia: A Critical Review of Synodal and Chronicle Sources (6th-14th Centuries) towards a Social History - Sánchez Sánchez, Xosé M. (Madrygal. Revista de Estudios Gallegos, 2024)
This article offers a critical review of the corpus of normative ecclesiastical and chronicle sources produced in the north-west of the Iberian Peninsula, with the aim of identifying materials that can sustain a social history of belief and superstition in the medieval Kingdom of Galicia. Focusing on popular practices and customs, it examines the individual and collective behaviours generated by these notions and their associated meanings. The study argues for the feasibility of a unified account –by topic, space, and period– across the longue durée of the Middle Ages. To that end, it critically analyses three key blocks of evidence: sixth-century catechetical works; synodal legislation and chronicle writing from the eleventh century onwards; and the corresponding materials from the thirteenth and fourteenth centuries. The analysis isolates practices and ideas that display temporal continuity in the north-west of the Peninsula, thereby enabling an initial, integrated interpretative framework.